SAT-230 Newly Diagnosed Schmidt’s Syndrome and Steroid Induced Psychosis - Soe, Myat Han (J Endocr Soc, 2020)
In 1926, Schmidt reported the combination of hypothyroidism and adrenal insufficiency (AI) with lymphocytic infiltration of both the thyroid and adrenal glands.1 This syndrome is now known as autoimmune polyendocrine syndrome (APS) type 2, characterized by two of the following three endocrinopathies: type 1 diabetes, autoimmune thyroiditis, and Addison’s disease.2 It may seem surprising that transient relative hypercortisolemia in AI patients at the beginning of treatment results in steroid induced psychosis (SIP). Here, we present a patient who developed SIP after starting steroid for AI. 44 year old Caucasian female with bipolar disorder and Hashimoto’s thyroiditis was admitted for generalized weakness, nausea, vomiting and weight loss of about 15 pounds in 3 months. On exam, blood pressure was 93/54 mmHg and pulse rate was 99. Her abdomen and arms looked hyperpigmented. Lab test revealed plasma glucose of 68 mg/dl, serum sodium of 129 mmol/l (133-145), potassium of 4.9 mmol/l (3.6 – 5.2), bicarbonate of 20 mmol/l (22 – 29). TSH was 16.93 mIU/ml (0.4 – 4.00) and FT4 was 0.74 ng/dl (0.7 1.8). CT abdomen and pelvis with contrast was unremarkable. As AI was suspected, cortisol level was checked and low at 0.5ug/dl. Cosyntropin stimulation test (CST) revealed pre-CST cortisol of 0.4 ug/dl, and post CST cortisol of 0.5 ug/dl at 45 min. ACTH was elevated at 514.4 pg/ml (7.2 – 63.3). A diagnosis of Schmidt’s syndrome was made based on elevated 21 hydroxylase of 8.5 U/ml (<1.0) and anti-thyroid peroxidase antibody of 20.5IU/ml (<5.6). Screening for type 1 diabetes and celiac disease was negative. After CST, stress dose hydrocortisone was started and dose was gradually tapered down in a few days. However, five days after steroid therapy, patient was admitted for suicidal ideation and catatonia which resolved quickly with Ativan and steroid taper to physiologic dose. APS type 2 has a prevalence of 1:1000. Clinicians should raise the suspicion for this syndrome in the appropriate context as seen in this patient presenting with classic features of AI. Although SIP in AI patients is not frequently reported, we should be mindful about this potential event especially in patients with underlying psychiatric illness. It is postulated that prolonged hypocortisolism in undiagnosed AI might lead to upregulation of central glucocorticoid receptors and hence glucocorticoid replacement might elicit a relative supraphysiological response in these patients.3